Jell-O : a biography - Wyman, Carolyn (Harcourt, 2001)
Offers a close-up look at the history of this popular fruit-flavored dessert, describing its marketing and sales strategies, detailing such offbeat uses for the product as JELL-O shots and JELL-O wrestling, and presenting a variety of common and unusual recipes.